2020
DOI: 10.2147/idr.s277681
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Comparative Study of Fluoroquinolone-Resistant Escherichia coli Lineages Portrays Indistinguishable Pathogenicity- and Survivability-Associated Phenotypic Characteristics Between ST1193 and ST131</p>

Abstract: Background: Sequence type 1193 is a new such lineage among fluoroquinolone-resistant Escherichia coli, which has risen dramatically within the last several years. However, reasons for rapid emergence and successful spread of E. coli ST1193 remain unclear. The aim of this study was to compare the pathogenicity and survivability features of E. coli ST1193 with global epidemic lineage, ST131. Methods: A total of 30 E. coli were used in this study. Isolates were divided into two groups, ST1193 (n=15) and ST131 (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Unlike earlier studies (36), ST1193 rather than ST405 was the second most prevalent sequence type in this study. ST1193 E. coli has increased dramatically in recent years and is emerging as a new, virulent, and resistant spectrum of fluoroquinolone-resistant E. coli (37,38), and our antimicrobial sensitivity tests suggested that ST1193 had a much higher rate of quinolone resistance than the other sequence type E. coli. Furthermore, ST1193 also had a high resistant rate to cephalosporins and ampicillin and the percentage of ESBLsproducers was 80.0%.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Unlike earlier studies (36), ST1193 rather than ST405 was the second most prevalent sequence type in this study. ST1193 E. coli has increased dramatically in recent years and is emerging as a new, virulent, and resistant spectrum of fluoroquinolone-resistant E. coli (37,38), and our antimicrobial sensitivity tests suggested that ST1193 had a much higher rate of quinolone resistance than the other sequence type E. coli. Furthermore, ST1193 also had a high resistant rate to cephalosporins and ampicillin and the percentage of ESBLsproducers was 80.0%.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, ST1193 also had a high resistant rate to cephalosporins and ampicillin and the percentage of ESBLs-producers was 80.0%. It has been reported that ST1193 was similar to ST131 in pathogenicity- and survivability-associated phenotypic characteristics ( 37 ) and its increase may be related to horizontal transfer of epidemic plasmid IncI1/ST16 ( 39 ). We need to pay attention to the wide spread of ST1193 and prevent the mass clonal spread of ST1193 like ST131.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increase in the number of E. coli strains resistant to ciprofloxacin has been observed. According to studies, this increase is mainly due to the dissemination of international clones ST131 (Subclones 131-H30-R and 131-H30Rx) and ST1193, which have mutations in the gyrA and parC genes that confer resistance to fluoroquinolones [80].…”
Section: Discussionmentioning
confidence: 99%
“…The serum resistance assay was performed twice in triplicates. E. coli EC505 (stored in our laboratory) was used as the positive control and E. coli DH5α was used as the negative control [ 41 , 52 ].…”
Section: Methodsmentioning
confidence: 99%